Copper Catalysis for Synthesizing Main‐Group Organometallics Containing B, Sn or Si. Issue 1 (20th January 2016) - Yoshida, Hiroto
Abstract: A copper complex has proven to be a potent catalyst for forming a C–B bond via diborylation of arynes and alkynes, affording vic ‐diborylarenes and vic ‐diborylalkenes with high efficiency. A boryl‐substituted organocopper species, which is intermediately generated in the diborylation, has been found to be captured by a tin or a carbon electrophile, leading to three‐component borylstannylation or carboboration, in which C–B and C–Sn (or C) bonds are constructed simultaneously. Furthermore, reducing the Lewis acidity of the boron center with 1, 8‐diaminonaphthalene decisively alters the regiochemical behavior of the borylcopper species, enabling the installation of a boryl moiety to occur at an internal carbon of terminal alkynes in borylstannylation and protoboration. Copper catalysis for C–Sn and C–Si bond‐forming processes via distannylation, hydrostannylation and silylstannylation, as well as silver catalysis for a C–B bond‐forming reaction, is also described. Abstract : Diborylation, borylstannylation and carboboration of unsaturated C–C bonds under copper catalysis are described. The synthesis of main‐group organometallics containing B, Sn or Si through copper‐catalyzed installation of a masked boryl, stannyl or silyl moiety is also presented.